“That single long year of Galba, Otho and Vitellius” (Tác. ’Dial’., 17): the civil wars of 69 AD - Belchior, Ygor Klein (Romanitas - Revista de Estudos Grecolatinos, 2013)
This article aims to analyze the limits of the main historiographical contributions on the Year of the Four Emperors. First of all, we start from an overview of the conflict arising after the government of Nero, highlighting the complexity of the period. Then, we intend to highlight the versions that this historiography has brought to us on the this subject to explain the fall of this controversial emperor, with the intention of presenting the approaches that researchers give to the conflicts of year 69 and their respective limits. After this exercise, we will propose a new way that leads us to think about the period in question beyond the methodological limits that were previously indicated by this work.